EKSEKUSI TERHADAP GADAI DEPOSITO BERJANGKA PADA PT. BANK YUDHA BHAKTI CABANG MEDAN - PUTRI RIZKITA SARI (PREMISE LAW JURNAL, 2015)
A debt deposit is a movable property and a pawned deposit object. Article 1154 of the Civil Code states that “in the case of a debtor is default, the creditor has the right to own the pawn property, and all contracts on this case are null and void.” A creditor’s practical reason to execute a pawned deposit is by asking the debtor to make an unconditional power of attorney for him to cash the deposit underhandedly. A profound study is needed to be conducted in order to analyze the execution of a pawned time deposit since the regulation on pawned deposit has not been adequate so far, and there is no specific and detailed regulation on it. Moreover, the binding of a pawned time deposit made by both a creditor and a debtor is submitted to both of them, while the payoff is depended on their underhanded agreement. The underhanded agreement is made based on the principle of freedom to enter into a contract. Keywords: Time Deposit, Pawned Deposit, Part of Execution